Therapeutic potential of cis-targeting bispecific antibodies - Oslund, Rob C.; Holland, Pamela M.; Lesley, Scott A.; Fadeyi, Olugbeminiyi O. (Cell chemical biology, 2024)
The growing clinical success of bispecific antibodies (bsAbs) has led to rapid interest in leveraging dual targeting in order to generate novel modes of therapeutic action beyond mono-targeting approaches. While bsAbs that bind targets on two different cells (trans-targeting) are showing promise in the clinic, the co-targeting of two proteins on the same cell surface through cis-targeting bsAbs (cis-bsAbs) is an emerging strategy to elicit new functionalities. This includes the ability to induce proximity, enhance binding to a target, increase target/cell selectivity, and/or co-modulate function on the cell surface with the goal of altering, reversing, or eradicating abnormal cellular activity that contributes to disease. In this review, we focus on the impact of cis-bsAbs in the clinic, their emerging applications, and untangle the intricacies of improving bsAb discovery and development. [Display omitted] Cis-targeting bispecific antibodies (cis-bsAbs) are a rapidly emerging approach for modulating cell surface environments to address unmet clinical need. Oslund et al. discuss the mechanistic and therapeutic impact of cis-bsAbs from early discovery to clinical stage. They also highlight key features for enhancing cis-bsAb discovery for next generation therapeutic development.